PENGARUH ECCENTRIC EXERCISE TERHADAP PENINGKATANKEMAMPUAN FUNGSIONAL ATLET DENGAN PATELLAR TENDINITIS (STUDI LITERATUR) - Anastasia Mutiara Kinya; Ganesa Puput Dinda Kurniawan; Nia Kurniawati (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Background: Patellar tendinitis is an overuse disorder of the patellar tendon which commonly occurs in sports athletes that require repetitive running and jumping movements. Patellar tendinitis can cause significant functional impairment in athletes requiring proper treatment. One of the treatments that can be done is eccentric exercise, it is thought to accelerate the alignment productivity of collagen fibers, produce stronger fibers, thereby reducing pain while increasing functional ability. Objective: To determine eccentrric exercise techniques that affect on increasing functional ability of athletes with patellartendinitis. Methods: This research type is a literature study with the independent variable eccentric exercise and the dependent variable functional ability. Study sample in athletes with patellar tendinitis. Data collection time is April 10, 2021, collected online through 4 search engines. Results: There are 7 literatures. The entire literature uses eccentric exercise to improve functional ability in athletes with patellar tendinitis measured using VISA-P. Conclusion: Eccentric exercise intervention has an effect on increasing functional ability in athletes with patellar tendnitis conditions.